Form & function of luxury mechanical watches : an archival study on the relationship between attributes and price - Tan, Zhi Qian (2013)
Luxury timepieces fall into a category of their own where their value is often misunderstood and difficult to quantify. In an attempt to comprehend luxury, studies exploring signalling theory have been conducted over the years. However, the intrinsic value of a luxury mechanical watch in terms of its form and function is an underdeveloped area of research that has the potential to reveal many new insights in how luxury can be valued as something tangible.